Anaesthetic Management for Caesarian Section Complicated with Eisenmenger Syndrome Concomitant Severe Preeclampsia: A Case Report - Yohanes Baptista; Muhammad Yurizar Yudhistira; RTH Supraptomo; Dympna Prameilita (HM Publisher, 2022)
Background: Although conception is discouraged in women with Eisenmenger syndrome, in inevitable circumstances, careful and meticulous planning of anesthesia can help the parturient survive the ordeal of a cesarean section. Anaesthetic management is aimed at avoiding haemodynamic changes that increase right-to-left shunt, thereby worsening hypoxemia. This study aimed to present a case of a pregnant woman with Eisenmenger syndrome who underwent caesarean section under general anesthesia management with severe preeclampsia. Case presentation: A 42-year-old pregnant woman (gravida 3, para 1, abortion 1) was admitted to our hospital at 38 weeks gestation with the chief complaint of shortness of breath and severe preeclampsia. Physical examination revealed cyanotic with clubbing fingers and elevated jugular venous pressure. Laboratory investigations did not reveal any abnormalities. Electrocardiography (ECG) shows normal sinus rhythm and right atrial deviation. General anesthesia was chosen due to obstetric complications, namely severe preeclampsia. The patient was premedicated with a gastroprotective agent, ranitidine 150 mg. At follow-up anesthesia 36 hours after surgery, the patient scored for maximum perioperative comfort and satisfaction. Conclusion: A multidisciplinary approach is needed to secure maternal and fetal survival for patients with Eisenmenger syndrome. Termination of Caesarean section under general anaesthesia may be the method of delivery that can be used, but care must be taken to avoid excessive and rapid blockade, dehydration, and hypoxaemia.